(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
Preserving the proteins native nature after their extraction is a strict requirement in immuno-chemical analysis, medical and food industry at receiving concentrates of viruses, bacteria and proteins. Anionic surfactant sodium dodecyl sulfate (SDS) is the most common detergent that is used for extraction and preconcentration of proteins. However, using of SDS solution often leads to denaturation of proteins and loss of their functional activity. Hydrotrope-induced micellar phase of the SDS (SDS-NaCl-H2Sal) is considered as a rational alternative to classical extragens, due to its ability to quantitatively extract of proteins molecules at pH close to the isoelectric point of the protein (pI) and at conditions of their positively charged forms domination (pH ≤ pI). From our point of view, using of the SDS-NaCl-H2Sal phase can provide a stabilization of the native state of proteins after their preconcentration. The objective of the work was to evaluete the possibility of proteins native state preservation after their preconcentration into SDS hydrotrope-induced phase. Peroxidase, catalase and nitrate reductase were chosen as protein model substrates. The change in the catalytic activity of these oxidoreductases in SDS micellar phase was used as indicator of proteins native state preservation. The activity of peroxidase and catalase was determined by the method of permanganametometric titration as the amount of H2O2 that was decomposed under the action of the enzyme. The activity of nitrate reductase was determined spectrophotometrically by the reaction of Griess reagent with nitrite ions formed as a result of the enzymatic decomposition of nitrates. It has been established that the catalytic activity of peroxidase, nitrate reductase and catalase in the SDS micellar phase increases in two, three and four times in comparison with the aqueous solution, respectively. Such rising of oxidoreductases catalytic activities after their preconcentration into the hydrotrope-induced phase of SDS confirms the preservation of proteins native nature.